Addressing ‘requests’ in Ambon: Appropriate Way to Ask a Request in Ambonese Community - Ahmad Rifani Talaohu (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
The notion of speech act as words or utterances used to say and do things in communication has been an interesting subject in linguistics field, especially in the cross-cultural communication. Among many speech act labels, request is the one that is commonly found in Indonesia, and even certain communities particularly in the eastern part (Ambonese) have their own way of delivering a request. This paper provides some data relating to request speech act and discusses how a request can affect the face of both speaker and hearer. Simply put in Ambon, the act of requesting something from someone cannot be carelessly carried out since several aspects such as cultural norms, social status, and even age differences must be taken into account. Moreover, politeness also holds crucial part in performing a request, as in a broader sense, when a speaker appears to have an impolite manner towards his/her interlocutor, it might potentially threaten the face of the hearer. And the result of losing a face will lead to a rejection of the request itself. Therefore, it is important to have an insight regarding how to perform a request appropriately in order to save someone’s face.